ANALISIS REGRESI LOGISTIK BINER UNTUK MENGETAHUI FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN DI BIMBINGAN BELAJAR PT. FADHIL KREATIF KOMUNIKA ATAU SNS - Kiki Alpiah (MathVisioN, 2023)
One of the problems that are often faced by tutoring institutions is student stop studying. This isi a serious proplem for a tutoring institution, including the Tutoring Institute PT. Fadhil Kreatif Komunika/SNS. This problem is greatly reduces the number of profits. There are factors that influence the studens of these tutoring institutions to stop studying. One of them is to Customer Loyalty. The purpose of thid research is to find the factors that influence customer loyslty in tutoring institute PT. Fadhil Kreatif Komunika/SNS. The research method is the binary logistic regression. The factors examined in this research are Service Quality, Costumer Satisfaction, Price and Tutor Competence. And the result of the analysis with α = 0,05 obtained a chi-square value of 122,802. Based on the the result of the Wald Test, the significant values was obtained greater than 0,05 on the variables of Service Quality and Tutor Competence, and the signigicant values was obtained less than 0,0t on the variables of Customer Satisfaction and Price. This means that there are variables that have a positive anf significant effecr on Customer Loyalty at PT. Fadhil Kreatif Komunika/SNS that is Customer Satisfaction and Price.